Determination of Bromate Ions in Drinking Water by Derivatization with 2-Methyl-2-Butene, Dispersive Liquid-Liquid Extraction and Gas Chromatography-Electron Capture Detection. (30th April 2020) - Nabi, Mehdi; Ghoreishi, Sayed Mehdi; Behpour, Mohsen
Abstract: Background: A simple, rapid, selective and sensitive sample preparation and derivatization method was performed for determination of bromate ions in water by means of dispersive liquid-liquid extraction (DLLE) by gas chromatography-electron capture detection (GC-ECD). This method is based on 2-methyl-2-butene derivatization by bromine produced from bromate ions in acidic medium and extraction by n-hexane. Objective: Derivatizing agent: It is cheap and available and it has high efficiency in reaction with Br2. Simplicity: Preparation and extraction process don't need to any specific equipment and procedure is completely simple and fast. Limit of detection: DL is as low as 0.43 µg/L. Methods: Various effective factors on the derivatization and extraction efficiency, such as amount of derivatizing agent, volume of extraction solvent, bromide concentration, volume and concentration of sulfuric acid, type and volume of extracting and dispersing solvent, ionic strength, storage time before extraction and ECD makeup-gas flow rate were investigated. Results: Under the optimum conditions, the method had a linear calibration curve ranging from 1.0 to 200.0 µg/L for bromate ions with a determination coefficient ( R 2 ) of 0.994 and the detection limit was 0.43 µg/L. The recovery percent and relative standard deviation for the determination of 1.0, 5.0 and 50.0 µg/L bromate ion was between 90 and 110%, and 3.0 and 8.0% ( n  = 3), respectively. Conclusions: Finally, the method was successfully applied for the preconcentration and determination of bromate ions in water samples, and satisfactory results were obtained. Highlights: (1) Fast, easy, accurate and economical innovative analysis of bromate ions in water and wastewater. (2) Determination of inorganic ion by GC-ECD after derivatization (3) Low detection limit (4) Optimization of different method parameters to obtain accurate results based on requirements of international standards, specifically ISO/IEC 17025.